SCIENTIFIC AND TECHNICAL TERMINOLOGY IN TEACHING FOREIGN LANGUAGES. - Mamajanova, Guncha (Журнал иностранных языков и лингвистики, 2023)
This article is devoted to the study of terminological vocabulary as the most rapidly developing part of the language vocabulary, directly reflecting everything new in various fields of science and production. The value of this lexical layer and its share in the general vocabulary of the language is constantly growing as a result of the rapid science and technology development and the associated continuous replenishment of the terminology of the relevant industries.